Development of visual attention control in early childhood: Associations with temperament and home environment - Moyano, Sebastián; Conejero, Ángela; Fernández, María; Serrano, Francisca; Rueda, M. Rosario (Frontiers in Psychology, 2022)
Endogenous visual attention orienting is early available from infancy. It shows a steady development during the preschool period towards monitoring and managing executive attention to optimize the interplay between environmental contingencies and internal goals. The current study aims at understanding this transition from basic forms of endogenous control of visual orienting towards the engagement of executive attention, as well as their association with individual differences in temperament and home environment. A total of 150 children between 2 and 4 years of age were evaluated in a Visual Sequence Learning task, measuring visual anticipations in easy (context-free) and complex (context-dependent) stimuli transitions. Results showed age to be a predictor of a reduction in exogenous attention, as well as increased abilities to attempt to anticipate and to correctly anticipate in complex transitions. Household disorganization predicted more complex correct anticipations, suggesting that the exposure to more unpredictable environments could benefit learning in context-dependent settings. Finally, temperamental surgency was found to be positively related to sustained attention in the task. Results are informative of age differences in visual attention control during toddlerhood and early childhood, and their association with temperament and home environment.